2017
DOI: 10.1093/geroni/igx016
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Support in Elder Financial Exploitation Using a Community Sample

Abstract: Background and ObjectiveSocial support is known to be an important protective factor against elder financial exploitation (FE), yet few empirical studies have examined the relationship between FE and distinct components of social support. Perceived social support, social network size, and interactions with close network members (positive and negative) were measured separately and tested as potential predictors of FE.Research Design and MethodsThree hundred and ninety-five community-dwelling adults aged 60 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 51 publications
0
22
1
Order By: Relevance
“…Numeracy and financial literacy have been found to be related to a wide range of financial outcomes, including increased retirement savings, and less vulnerability to financial exploitation in older adults (Wood & Lichtenberg, 2017). Negative social interaction may increase vulnerability secondary to a lack of a sounding board regarding a financial decision, or increase willingness to call a stranger listed in a solicitation (Liu, Wood, Xi, Berger, & Wilber, 2017). Thus, individual differences such as risk perception, numeracy, loneliness, and general financial status may influence an individual’s decision to respond to MMS solicitations.…”
mentioning
confidence: 99%
“…Numeracy and financial literacy have been found to be related to a wide range of financial outcomes, including increased retirement savings, and less vulnerability to financial exploitation in older adults (Wood & Lichtenberg, 2017). Negative social interaction may increase vulnerability secondary to a lack of a sounding board regarding a financial decision, or increase willingness to call a stranger listed in a solicitation (Liu, Wood, Xi, Berger, & Wilber, 2017). Thus, individual differences such as risk perception, numeracy, loneliness, and general financial status may influence an individual’s decision to respond to MMS solicitations.…”
mentioning
confidence: 99%
“…Ferraro and LaGrange [19] found that fear of crime index is lowest for those aged 55-64, highest for those aged 18-24 and slightly higher for the aged 65-74 and 75+. Physical health and depression were found to be predictive of elder financial exploitation; that is, older adults with poorer physical health and higher risk of depression experience higher victimization of financial exploitation [20]. Similarly, using a focus group of 45 stakeholders in Hong Kong, Li et al [5] found that older individuals with declining health were suitable targets for financial fraud.…”
Section: Vulnerability Perspectivementioning
confidence: 99%
“…Guanxi-close relationships in the immediate neighborhood-has been confirmed as a significant indicator of fear of crime in contemporary urban China [23]. In a study of older adults in the U.S., Liu et al [20] found that negative interactions with close network members and lower perceived social support significantly predicted greater financial exploitation risk. However, social network size and positive interactions with close network members were not associated with financial exploitation risk.…”
Section: Vulnerability Perspectivementioning
confidence: 99%
“…More recently, Liu et al (2017b) found that it was specifically negative interactions with those in their social network that uniquely predicted financial exploitation, not network size. Regarding gender, unequivocally more women than men are the victims of financial exploitation, and yet gender fails to emerge in any study using multivariate analysis (Jackson 2017b).…”
Section: Financial Abuse Risk Factors In An Ecological Contextmentioning
confidence: 99%